2016
DOI: 10.1016/j.drugalcdep.2015.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Moderators and mediators of the relationship between receiving versus being denied a pregnancy termination and subsequent binge drinking

Abstract: Background Women who terminate pregnancies drink more subsequent to the pregnancy than women who give birth, including women who give birth after seeking to terminate a pregnancy. Methods Data are from the Turnaway Study, a prospective, longitudinal study of 956 women who sought to terminate pregnancies at 30 U.S. facilities. This paper focuses on the 452 women who received terminations just below facility gestational limits and 231 who were denied terminations because they presented just beyond facility ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We did not find differences in potential alcohol problem symptoms (eye-opener or blackout) or in drug use between groups (Roberts et al, 2014(Roberts et al, , 2015. We also did not find evidence that having abortions increased heavy episodic alcohol, problem alcohol, tobacco, or drug use or that differences in heavy episodic alcohol use between groups were explained by stress or negative emotions about the pregnancy Roberts et al, 2014Roberts et al, , 2015Roberts et al, , 2016. Together, these findings indicate that-over 2 to 2.5 years-women continuing unwanted pregnancies reduce/cease some, but not all, substance use, whereas women who have abortions tend to continue substance use patterns from before their abortions.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…We did not find differences in potential alcohol problem symptoms (eye-opener or blackout) or in drug use between groups (Roberts et al, 2014(Roberts et al, , 2015. We also did not find evidence that having abortions increased heavy episodic alcohol, problem alcohol, tobacco, or drug use or that differences in heavy episodic alcohol use between groups were explained by stress or negative emotions about the pregnancy Roberts et al, 2014Roberts et al, , 2015Roberts et al, , 2016. Together, these findings indicate that-over 2 to 2.5 years-women continuing unwanted pregnancies reduce/cease some, but not all, substance use, whereas women who have abortions tend to continue substance use patterns from before their abortions.…”
mentioning
confidence: 55%
“…In addition to broader mental health (Biggs et al, 2015(Biggs et al, , 2016(Biggs et al, , 2017Foster et al, 2015), the Turnaway Study includes assessment of ATOD use and alcohol misuse. We have published mid-study (2-to 2.5-year) findings for ATOD use Roberts et al, 2014Roberts et al, , 2015Roberts et al, , 2016. We found that women who had abortions had higher levels of any alcohol use, heavy episodic alcohol use, and tobacco use over 2 to 2.5 years than women denied abortions, but these differences were attributable to reductions among women denied , not increases among women receiving, abortions.…”
mentioning
confidence: 88%